Needs of family care givers of stroke patients receiving care at the university teaching hospital, Lusaka - Kambobe Wesley (Lusaka, the university of Zambia, school of medicine, 2016)
Following a stroke patient often suffer from varying degrees of disability that require acute impatient treatment and extended care at home. Due to the extended care at home, the caregivers assume multiple responsibilities that can result in stress, particularly when thier own needs are inadequately addressed during the patient's recovery.
Dissertation submitted in partial fulfilment for the award of bachelors degree in nursing sciences at the university of Zambia.
Includes bibliographic references.
Keywords: Caregivers